2017
DOI: 10.1016/j.gpb.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Acetylation and Deacetylation in Brain Development and Neuropathies

Abstract: Embryonic development is critical for the final functionality and maintenance of the adult brain. Brain development is tightly regulated by intracellular and extracellular signaling. Lysine acetylation and deacetylation are posttranslational modifications that are able to link extracellular signals to intracellular responses. A wealth of evidence indicates that lysine acetylation and deacetylation are critical for brain development and functionality. Indeed, mutations of the enzymes and cofactors responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 171 publications
0
48
0
1
Order By: Relevance
“…The literature shows that ADHD has been associated with weaker function of the prefrontal cortex compared to healthy individuals 13 . KAT2B is a lysine histone acetyltranferase highly expressed in the brain 14 . Previous evidence has suggested that lysine acetylation is importance for brain function and proper development 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that ADHD has been associated with weaker function of the prefrontal cortex compared to healthy individuals 13 . KAT2B is a lysine histone acetyltranferase highly expressed in the brain 14 . Previous evidence has suggested that lysine acetylation is importance for brain function and proper development 14 .…”
Section: Discussionmentioning
confidence: 99%
“…KAT2B is a lysine histone acetyltranferase highly expressed in the brain 14 . Previous evidence has suggested that lysine acetylation is importance for brain function and proper development 14 . At another locus, TMEM161B, a transmembrane protein, had the highest posterior inclusion probability of 0.838 in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four ASD-related FMRP targets we found, Kat6a and Kmt2c are previously suggested to be FMRP mRNA targets from ribosomal profiling using adult neurons (Darnell et al, 2011). Kat6a and Kmt2c are histone modification writers, which can epigenetically regulate transcription (Shen et al, 2014;Tapias and Wang, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…TAF7 was reported to play a critical role in embryonic development [32]. KAT2A, ATF2 and TAF1 were also suggested to be included in brain development [33]. BRCA1 has been shown to play critical roles in brain development [34].…”
Section: Resultsmentioning
confidence: 99%